2021
DOI: 10.3390/jcm10051043
|View full text |Cite
|
Sign up to set email alerts
|

The Analgesic Efficacy of Nefopam in Patient-Controlled Analgesia after Laparoscopic Gynecologic Surgery: A Randomized, Double-Blind, Non-Inferiority Study

Abstract: Opioid-sparing effects of nefopam during patient-controlled analgesia (PCA) are well demonstrated. We hypothesized that postoperative pain control with an opioid-equivalent dose of nefopam as a single analgesic agent for PCA would not be inferior to fentanyl in laparoscopic gynecologic surgery. In total, 135 patients were randomly assigned to the N (nefopam 200 mg), NF (fentanyl 500 mcg + nefopam 100 mg), and F (fentanyl 1000 mcg) groups (n = 45 patients per group). The primary outcome was the numerical rating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…These results were consistent with previous studies, demonstrating the effectiveness of nefopam, whether used as an adjuvant or as a substitute for opioids in PCA, for achieving effective and comparable pain control after surgery [ 6 , 7 , 8 , 9 , 10 ]. Kim et al reported that nefopam alone provided sufficient analgesic effect following cardiac surgery.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These results were consistent with previous studies, demonstrating the effectiveness of nefopam, whether used as an adjuvant or as a substitute for opioids in PCA, for achieving effective and comparable pain control after surgery [ 6 , 7 , 8 , 9 , 10 ]. Kim et al reported that nefopam alone provided sufficient analgesic effect following cardiac surgery.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have yielded conflicting results regarding PONV incidence when using nefopam as a postoperative analgesic. Some studies have suggested that nefopam itself may not decrease PONV [ 6 , 7 , 8 , 13 ] due to its emetic properties [ 14 , 15 ]. However, others have reported that nefopam use could reduce opioid consumption, thereby reducing PONV incidence [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Capsicum plaster at classical Chinese acupoints is an alternative to acupuncture, which has been reported to be an effective method for reducing postoperative pain and PONV when applied to the acupuncture points [ 36 ]. Nefopam is a non-opioid, non-steroidal centrally acting analgesic that has been used as an alternative to opioids to control mild to moderate pain [ 37 ]. Nefopam was shown to provide similar postoperative analgesia to ketorolac when used as an adjuvant analgesic with fentanyl-based PCA [ 38 ].…”
Section: Discussionmentioning
confidence: 99%